2018
DOI: 10.1002/jbmr.3558
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Receptor γ Activity in Mesenchymal Stem Cells Regulates Endochondral Bone, Angiogenesis, and B Lymphopoiesis

Abstract: Retinoic acid receptor (RAR) signaling regulates bone structure and hematopoiesis through intrinsic and extrinsic mechanisms. This study aimed to establish how early in the osteoblast lineage loss of RARγ (Rarg) disrupts the bone marrow microenvironment. Bone structure was analyzed by micro-computed tomography (μCT) in Rarg mice and mice with Rarg conditional deletion in Osterix-Cre-targeted osteoblast progenitors or Prrx1-Cre-targeted mesenchymal stem cells. Rarg tibias exhibited less trabecular and cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 61 publications
3
34
0
Order By: Relevance
“…It has long been known that RARs are nuclear receptors that play an important role in the proliferation and differentiation of numerous cell lines. Several studies have shown that RARs have a direct role both in hematopoiesis and in non-hematopoietic cells present in the bone marrow (BM) microenvironment and which also influence the correct process of hematopoiesis [127] (Figure 2). The utilization of ATRA to differentiate leukemic cells block at the promyelocytic stage in patients with APL is a first example of the importance of retinoids signaling in the process of differentiation of hematopoietic cells [128].…”
Section: The Complex Role Of Rars In the Regulation Of Hematopoietmentioning
confidence: 99%
“…It has long been known that RARs are nuclear receptors that play an important role in the proliferation and differentiation of numerous cell lines. Several studies have shown that RARs have a direct role both in hematopoiesis and in non-hematopoietic cells present in the bone marrow (BM) microenvironment and which also influence the correct process of hematopoiesis [127] (Figure 2). The utilization of ATRA to differentiate leukemic cells block at the promyelocytic stage in patients with APL is a first example of the importance of retinoids signaling in the process of differentiation of hematopoietic cells [128].…”
Section: The Complex Role Of Rars In the Regulation Of Hematopoietmentioning
confidence: 99%
“…49,50 RARγ activity in mesenchymal stem cells plays a role in regulating endochondral bone. 51 Green et al report that RARγ is a negative regulator of osteoclastogenesis in vivo and in vitro. 49 However, hitherto, there are few publications reporting the involvement of different receptors in the ATRA's inhibitive effects of BMPinduced osteoblastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the endocortical surface, these receptors appear to be expressed in both proliferating preosteoblasts and terminally differentiated osteoblasts. We cannot exclude, however, that the effects on osteoblasts may be due to extrinsic effects mediated by other cell types in the bone microenvironment expressing RARs, because it has recently been shown that deletion in mice of Rarg in Prxx1 -expressing limb bud–derived mesenchymal stem cells results in not only decreased trabecular bone mass but also in effects on angiogenesis and B-lymphopoiesis ( 51 ). It seems that the decrease in cortical thickness observed in mice with global deletion of Rarg may also be caused by extrinsic effects, because this effect was not observed in mice with deletion of Rarg in Prxx1 - or Sp7 -expressing cells.…”
Section: Discussionmentioning
confidence: 99%